Analisis Terhadap Penyebab Terjadinya Kebanjiran Di Kota Medan Akibat Pencemaran Lingkungan Perspektif Undang-Undang Nomor 32 Tahun 2009 - Fahrizal S.Siagian; Geofani Milthree Saragih; David Chrisna Pangihutan; Frans Maruli Silaban; Gamal Abdul Nasser; Muhammad Hanafie Arrasyid (International Forum of Researchers and Lecturers, 2024)
This research analyzes the causes of flooding in Medan City due to environmental pollution, with the perspective of Law Number 32 of 2009 concerning Environmental Protection and Management (UU-PPLH). Medan City is one of the flood-prone areas in North Sumatra, which experiences flooding almost every year. Factors that cause flooding include poor city drainage systems and environmental pollution due to careless dumping of rubbish. Law Number 32 of 2009 regulates environmental management and protection, but its implementation is not yet optimal. The research method used is normative legal research with a document study and field observation approach. The research results show that public awareness of the importance of waste management and environmental preservation is still low, which contributes to flooding. There is a need to increase supervision and law enforcement as well as educate the public to reduce the risk of flooding in the future.